2012
DOI: 10.1021/bm300332w
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Derived Extracellular Matrix Enables Survival and Multilineage Differentiation within Superporous Hydrogels

Abstract: Hydrophilic poly(ethylene glycol) diacrylate (PEGDA) hydrogel surfaces resist protein adsorption and are generally thought to be unsuitable for anchorage dependent cells to adhere. Intriguingly, our previous findings revealed that PEGDA superporous hydrogel scaffolds (SPHs) allow anchorage of bone marrow derived human mesenchymal stem cells (hMSCs) and support their long term survival. Therefore, we hypothesized that the physicochemical characteristics of the scaffold impart properties that could foster cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…For instance, an extensive expression of laminin was observed in vitro following three weeks of chondrogenic culture of bone marrow-derived mesenchymal stem cells (MSCs) in both poly (ethylene glycol) diacrylate (PEGDA) hydrogel (Köllmer et al, 2012) and hyaluronic acidbased hydrogel (Toh et al, 2012). Similarly, Jeng et al (2012Jeng et al ( , 2013 found widespread expression of laminins throughout the ECM, in both engineered cartilage constructs and reparative tissues, following implantation of chondrocyte-seeded constructs in caprine cartilage defects -although the expression of laminin appeared diffused compared to the pericellular staining pattern observed in normal adult cartilage.…”
Section: Y Sun Et Almentioning
confidence: 99%
“…For instance, an extensive expression of laminin was observed in vitro following three weeks of chondrogenic culture of bone marrow-derived mesenchymal stem cells (MSCs) in both poly (ethylene glycol) diacrylate (PEGDA) hydrogel (Köllmer et al, 2012) and hyaluronic acidbased hydrogel (Toh et al, 2012). Similarly, Jeng et al (2012Jeng et al ( , 2013 found widespread expression of laminins throughout the ECM, in both engineered cartilage constructs and reparative tissues, following implantation of chondrocyte-seeded constructs in caprine cartilage defects -although the expression of laminin appeared diffused compared to the pericellular staining pattern observed in normal adult cartilage.…”
Section: Y Sun Et Almentioning
confidence: 99%
“…In vitro cell culture studies were conducted according to the literature [45,46]. The ability of human embryonic lung diploid fibroblast cells and H9c2 cardiac muscle cells to grow into the hydrogels 3D structure was assessed.…”
Section: In Vitro Cell Culturementioning
confidence: 99%
“…32,33,45,48 However, this technique is limited in that the user must select a panel of antibodies targeting proteins of interest. Here, we pair shotgun proteomics and immunostaining to circumvent the need for a priori knowledge of what proteins the cells may be secreting.…”
Section: Summary/discussionmentioning
confidence: 99%